SYSTEMATIC LITERATURE REVIEW: PENERAPAN DIGITAL MARKETING SEBAGAI STRATEGI PROMOSI DALAM MENINGKATKAN MINAT CALON PESERTA DIDIK BARU DI LEMBAGA PENDIDIKAN - Lestari, Lusi; Sumyati, Lilis; Fauzi, Anis (Jurnal Manajemen dan Pemasaran, 2025)
Modern educational institutions must be managed with great competence and care due to the increasing intensity of competition among schools. To influence the choices of parents and prospective students, schools need effective promotional strategies. In today’s fast-paced technological era, reaching tech-savvy audiences requires educational institutions to adapt by incorporating digital marketing into their strategies. Schools can leverage platforms like official websites and social media channels such as Facebook, Instagram, Twitter, TikTok, YouTube, and WhatsApp for this purpose.This study explores how digital marketing-based promotional strategies can enhance the interest of potential new students. Using a literature review approach, it draws insights from various sources, including books, research findings, and academic journals. When implemented effectively, digital marketing enables schools to engage a broader audience, making information about the institution easily accessible anytime and anywhere. Additionally, these digital promotional efforts are both cost-effective and efficient, supporting schools in their mission to attract new students successfully.